An introduction to CBT research - Rakovshik, Sarah (London : SAGE Publications Ltd, 2020)
This highly practical book will guide students through the different levels of research within CBT by addressing the general principles of grappling with evidence and understanding statistics. It also highlights how to critically engage with, interpret and evaluate research so that it can be used to shape practice. This important book will help readers see the relevance of research in their working lives and empower them to become active and keen researchers.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Research -- Evaluation